186. Salvage Low Dose Rate Brachytherapy (SBT) For Recurrent Prostate Cancer (PC) After External Beam Radiotherapy (EBRT) at Spedali Civili of Brescia: Dosimetric Results. (December 2018) - Ghedi, B.; Fiume, A.; Saiani, F.; Barbera, F.; Vitali, P.; Triggiani, L.; Moretti, R.
Abstract: Purpose: New developments in prostate brachytherapy include its use in salvage treatment following relapse in patients who received prior radiotherapy. We report the dosimetric results of our monoinstitutional experience at Spedali Civili of Brescia. Methods and materials: From June 2012 to November 2015, 19 patients with radiologically confirmed local recurrence of PC after primary EBRT underwent low dose rate (LDR) SBT with permanent implant of 125-I, with an initial air-kerma strength of 0.520 U. Eligibility criteria: negative systemic staging, good urinary and bowel function, prostate volume <50 cm 3 . The physical delivered dose to the planning target volume (the whole prostate gland plus a 2-mm margin to include all microscopic disease and physical uncertainties) was 130 Gy, corresponding to an EQD2 = 79.4 Gy, considering the radiobiological values of α / β = 3 Gy and repair half-time T1/2 = 0.27 h. Target volume and critical organs (OAR), such as urethra and rectum, were outlined on transverse images spaced 5 mm. The volume study was performed by a BKMedical Pro-Focus transrectal ultrasound. To reduce prostate movement during the procedure, 2 stabilizing needles were inserted. An intraoperative planning was performed using the VariSeed Software combining automatic and manual positioning of preloaded needles and optimizing the results. During the procedure, fluoroscopic images were taken to check the implant and the number of seeds. Results: The dose-volume parameters for PTV and organs at risk are summarized in the Table. 16 over 19 patients (84%) had no toxicity. 1 of 19 had a G4 rectal toxicity, although the rectum tolerance doses were well respected. 2 of 19 patients registered G3 late genitourinary toxicity. Conclusion: Despite the short median follow-up period after SBT (24 months) and the small number of treated patients, the present work seems to confirm the effectiveness of the LDR-SBT treatment for local PC relapse.